Early predominant inflammatory myopathy in anti‐glycyl‐tRNA synthetase (EJ) antibody positive antisynthetase syndrome. Issue 3 (15th January 2021) - Warner, Robin; Reid, Derrece
Abstract: It is important to consider antisynthetase syndrome in the differential diagnosis of patients presenting with weakness, respiratory distress, and a constellation of complaints spanning multiple organ systems, as this will change clinical management. Abstract : It is important to consider antisynthetase syndrome in the differential diagnosis of patients presenting with weakness, respiratory distress, and a constellation of complaints spanning multiple organ systems, as this will change clinical management.